Understanding the automotive industry: German OEM behaviour during the last 20 years and its implications - Mazur,C; Contestabile,M; Offer,GJ; Brandon,NP (2014)
This work presents a study of how the automotive industry has responded in the last 20 years to pressures driven by economic and environmental issues, and by the transition towards electric mobility. Timelines for the major German automotive OEMs are presented to understand the industry's behaviour in the past in order to design suitable policies that are appropriate to reach future goals around the electrification of road transport. Based upon a comparison of the pressures arising in the automotive sector and the companies' behaviour with regard to technology choice and R&D, a set of hypotheses concerning this behaviour is then presented.